A companion to urban anthropology - Nonini, Donald Macon (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2014)
"A Companion to Urban Anthropology presents original essays on central concepts in urban anthropology and ethnography"--
Includes index.
Machine generated contents note: Preface Notes on Contributors Introduction Donald M. Nonini Part 1: Foundational Concepts: Affirmed and Contested 1. Spatialities Setha Low 2. Flows Gary W. McDonogh 3. Community John Clarke 4. Citizenship Sian Lazar Part 2: Materializations and Their Imaginaries 5. Built Structures and Planning Deborah Pellow and Denise Lawrence-Zuniga 6. Borders Thomas M. Wilson 7. Markets Linda J. Seligmann 8. Cars and Transport Catherine Lutz Part 3: Dividing Processes, Bases of Solidarity 9. Class Don Kalb 10. Gender Ida Susser 11. Sexualities Ara Wilson 12. Race Brett Williams 13. Extralegality Alan Smart and Filippo Zerilli Part 4: Abstractions of Consequence 14. Global Systems and Globalization Jonathan Friedman 15. Governance Jeffrey Maskovsky and Julian Brash 16. Policing and Security Josiah McC. Heyman 17. Transnationality Nina Glick Schiller 18. Cosmopolitanism Pnina Werbner Part 5: Experiencing/Knowing the City in Everyday Life 19. Practices of Sociality Jose Guilherme Cantor Magnani 20. Memory and Narrative Lindsay DuBois 21. Religion Thomas Blom Hansen Part 6: Nature and the City 22. Nature Robert Rotenberg 23. Food and Farming Donald M. Nonini 24. Pollution Eveline Durr and Rivke Jaffe 25. Resilience Stephan Barthel Part 7: Challenging the Present, Transforming Futures 26. Commons, The Maribel Casas-Cortes, Sebastian Cobarrubias, and John Pickles 27. Social Movements Michal Osterweil 28. Futures Hilary Cunningham and Stephen Bede Sharper Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Urban anthropology; SOCIAL SCIENCE / Anthropology / Cultural; Urban anthropology; Electronic books; Electronic books